FACTORS RELATED TO QUALITY OF LIFE IN CORONARY HEART DISEASE PATIENTS AT CARDIAC POLYCLINIC DR. M. DJAMIL PADANG HOSPITAL - Laksmana, Rio; Afriyanti, Esi; Bawono, Agus Sri (Menara Medika, 2025)
Pendahuluan: Penyakit jantung koroner (PJK) adalah salah satu penyakit kardiovaskular yang menyebabkan kematian tertinggi, yaitu sebanyak 35% dari penyebab kematian di seluruh dunia. Kualitas hidup yang baik pada pasien PJK diperlukan untuk menjaga status kesehatan yang optimal. Tujuan: Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kualitas hidup pasien PJK di Poliklinik Jantung RSUD Pusat Dr. M. Djamil Padang. Metode: Penelitian ini menggunakan desain analitik dengan pendekatan cross-sectional studi, dengan jumlah sampel 94 orang dengan teknik purposive sampling. Data dikumpulkan menggunakan Kuesioner the Seattle Angina Questionnaire (SAQ-7), the Social Support Questionnaire, the Cardiac Anxiety Questionnaire (CAQ), dan the Cardiac Self-Efficacy Scales. Hasil: Hasil penelitian ini menunjukkan bahwa rata-rata kualitas hidup pasien PJK adalah 42,72. Ada hubungan antara dukungan keluarga (p-value = 0,001 dan r = 0,93), ansietas (p-value = 0,003 dan r = -0,67), dan efikasi diri (p-value = 0,032 dan r = 0,49) dengan kualitas hidup pasien PJK. Faktor yang mempengaruhi kualitas hidup pasien PJK adalah dukungan keluarga, ansietas, dan efikasi diri, sebanyak 80,2% (R2 = 0,082), dengan faktor yang paling dominan adalah dukungan keluarga, yaitu 89,1% (B = 0,891). Kesimpulan: berdasarkan hasil penelitian ini, diharapkan perawat dapat memberikan dukungan informasi berupa edukasi kesehatan kepada pasien PJK dan caregiver, terutama mengenai menjaga stabilitas angina, sehingga dapat menjaga kualitas hidup yang baik pada pasien PJK.Kata kunci: Penyakit Jantung Koroner (PJK), Kualitas Hidup, Dukungan Keluarga, Ansietas, Efikasi Diri.ABSTRACTBackground: Coronary heart disease (CHD) is one of the cardiovascular diseases that causes the highest mortality, which is as much as 35% of the causes of death worldwide. A good quality of life in patients with CHD is needed to maintain optimal health status. Objective: This study aims to determine the factors influencing the quality of life of CHD patients at the Cardiac Polyclinic of the Central General Hospital Dr. M. Djamil Padang. Method: This study used an analytic design with a cross-sectional study approach, with a sample size of 94 people and a purposive sampling technique. Data was collected using the Seattle Angina Questionnaire (SAQ-7), the Social Support Questionnaire, the Cardiac Anxiety Questionnaire (CAQ), and the Cardiac Self-Efficacy Scales. Results: The results of this study indicate that the average quality of life of CHD patients is 42.72, which is low compared to the maximum quality of life value of 100. There is a relationship between family support (p-value = 0.001 and r = 0.93), anxiety (p-value = 0.003 and r = -0.67), and self-efficacy (p-value = 0.032 and r = 0.49) on the quality of life of these CHD patients. Factors affecting CHD patients' quality of life are family support, anxiety, and self-efficacy, as much as 80.2% (R2 = 0.082), with the most dominant factor being family support, which is 89.1% (B = 0.891). Conclusions: With the results of this study, it is hoped that nurses can provide informational support in the form of health education to CHD patients and caregivers, especially regarding maintaining angina stability, so that they can maintain a good quality of life in CHD patientsKeywords: Coronary Heart Disease (CHD), Quality of Life, Family Support, Anxiety, Self-Efficacy.